Parametric study for head injury criteria response of three-year olds in a child restraint system in oblique and lateral intrusive side impact - Shasthri, Sevaguru; Venkatason, Kausalyah; Shah, Qasim Hussain; Abdullah, Kassim Abdulrahman; Idres, Moumen; Wong, Sha Voon (Taylor & Francis, 2014)
A parametric study is undertaken to ascertain the sensitivity of the child restraint system (CRS) design, with respect to oblique side impact at standard velocities in consideration of intrusion. A hybrid model is constructed using a combination of both finite elements and multi-body ellipsoids where a three-year-old Hybrid III child dummy is placed inside a CRS and restrained with a harness system. A prescribed structural motion simulation of a side-impact crash is carried out based on experimental data. Validation is performed and the model is shown to be acceptable for common standard injury responses as well as being greatly economical in terms of computational processing time. A plan of experiments is prepared based on the Latin hypercube sampling for six parameters involving two different crash velocities. The head injury criterion (HIC) is considered as the response in this study. The model is adapted for intrusion and oblique impact. Response surface models are shown to be suitable for the mathematical modelling of the problem and Student’s t-test is used to assess the parameter sensitivity both qualitatively and quantitatively. Most of the parameters are seen to have greater significance for wider principle direction of force (PDOF) angles above 60°. In general, a gradual decrease in significance is observed for parameters with increasing impact velocity, with the notable exception of the impact angle. The impact angle is shown to most notably affect the HIC especially from PDOF angles 45°-75°, identified as the critical impact angle range. The far side shoulder harness slack parameter is also found to be significant in reducing the HIC.